Graphite flame retardant applied on polyester textiles: flammable, thermal and in vitro toxicological analysis. Issue 3 (June 2022) - Alonso, Cristina; Manich, Albert; Campo, Adolfo del; Felix-De Castro, Paula; Boisseree, Nora; Coderch, Luisa; Martí, Meritxell
Expandable graphite was applied to an upholstery polyester textile material as an eco-friendly flame-retardant alternative to halogenated compounds. Fabrics treated with the flame retardant were evaluated by flammability tests. Besides, thermal analysis was carried out by Differential Scanning Calorimetry (DSC) and Thermogravimetric Analysis (TGA). Moreover, a percutaneous absorption study was conducted to verify the safety in terms of dermal penetration of the flame-retardant treated upholstery fabric for human use. The upholstery fabric treated with expandable graphite successfully passed the flammability tests. Thermogravimetric analyses with TGA and DSC showed that the flame-retardant application slightly decreased the initial decomposition temperatures regardless of the atmosphere but increased the final residue at 600°C (35.7% in O2 and 44.5% in N2 ) compared to non-treated upholstered fabrics. Dermal permeation of expandable graphite applied on the polyester fabric showed no penetration after 24 h of fabric exposure time. This result demonstrated that graphite-treated polyester fabric is dermatologically and toxicologically safe for use in upholstery. Applied expandable graphite proved an efficient and safe flame-retardant alternative to conventional flame retardants for eco-friendly flame resistance applications in upholstery fabrics.